ISSUES AND CHALLENGES IN THE IMPLEMENTATION OF THE INTEGRATION OF KNOWLEDGE IN ISLAM IN NIGERIAN UNIVERSITIES - Aliyu Idris,; Prof. Dr. Mohd Nor Bin Nawawi, (Journal of Islamic, Social, Economics and Development, 2021)
The study was aimed to highlight the concept of integration of Knowledge inIslam and the challenges confronting the smooth implementation of the concept in BayeroUniversity, Kano, Nigeria. The integration of knowledge is a concept which can be appliedby the educational sector in order to create a sound generation of multidisciplinaryknowledge. The concept of integration of knowledge can be define as a union of two ormore sectors as a merger or combination of both western and Islamic knowledge. Muslimswere mandated to seek for knowledge, which includes various forms of knowledge such asAqidah, Shariah, Moral, Ethics and others. Mastering the Islamic knowledge along withthe western knowledge may lead to the emergence of contemporary knowledge based onthe Islamic principles. Islam has encouraged the Muslims to seek for knowledge in all thefields that will assist the humanity. The Study adopted the qualitative research isconducted in order to have better understanding on the interpretations and meaning thatpeople give to events, objects and other people in their environmental contexts. The Paperconclude that the application of western knowledge leads to the spread of secular influencein the educational system of a nation, which in turn leads to the gradual loss of Islamicidentity of the society. Therefore, the approach to the integration of Islamic knowledgeand that of the West needs to be seen as an alternative for the society in leading theireveryday lives based on the true teachings of Islam.